2015
DOI: 10.14814/phy2.12442
|View full text |Cite
|
Sign up to set email alerts
|

The cytohesin guanosine exchange factors (GEFs) are required to promote HGF-mediated renal recovery after acute kidney injury (AKI) in mice

Abstract: The lack of current treatment and preventable measures for acute kidney injury (AKI) in hospitalized patients results in an increased mortality rate of up to 80% and elevated health costs. Additionally, if not properly repaired, those who survive AKI may develop fibrosis and long-term kidney damage. The molecular aspects of kidney injury and repair are still uncertain. Hepatocyte growth factor (HGF) promotes recovery of the injured kidney by inducing survival and migration of tubular epithelial cells to repopu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 38 publications
0
24
0
Order By: Relevance
“…To date, secinH3 has been rarely applied in vivo. The existing studies did not focus on possible hemodynamic effects, and therefore none have been reported to date (22,50). SecinH3 was tolerated for a minimum of 2-4 days in mice, although it induced hepatic insulin resistance (22,50).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, secinH3 has been rarely applied in vivo. The existing studies did not focus on possible hemodynamic effects, and therefore none have been reported to date (22,50). SecinH3 was tolerated for a minimum of 2-4 days in mice, although it induced hepatic insulin resistance (22,50).…”
Section: Discussionmentioning
confidence: 99%
“…Whereas the roles of RhoA and Rac, as well as their effector kinases, have been well established for contraction of prostate smooth muscle, no data on the involvement of GEFs or about the activating mechanisms of these GTPases in the prostate are available to date (14,26,55,63). Cytohesins are a group of GEFs, which exist in four different isoforms, referred to as cytohesin-1Ϫ4 (33,37,50). Apart from indirect, downstream Rac activation by cytohesin-dependent mechanisms, direct activation of ADP ribosylation factor 6 (ARF6) by cytohesin-2 has been repeatedly reported (30,33,50,57).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8H-L,N). We also examined the distribution of activated ARF6 using an ARF6-GTP antibody (Torii et al, 2014;Reviriego-Mendoza and Santy, 2015). Levels of ARF6-GTP peaked around P8 ( Fig.…”
Section: Arf6-gtp Labeling Peaks At P8 In Developing Utriclesmentioning
confidence: 99%
“…In addition to the skin, other tissues, such as liver, lung and kidney, express Arf62345, suggesting that Arf6 plays an key role in wound healing-related pathophysiological phenomena in these tissues. In support of this assumption, cytohesin family members of Arf6 GEFs, which regulate Arf6 activity, are required for the HGF/c-Met signaling-dependent recovery of acute kidney injury46. Thus, it is of interesting to investigate pathophysiological roles of HGF/c-Met/Arf6 signaling in a wide variety of tissues.…”
Section: Discussionmentioning
confidence: 94%